Histopathological Spectrum and Immunohistochemistry Expression of Pediatric Solid Malignant Tumors: An Observational Study - Bhumika Patel; Jagadale Kunda; Reena Bharadwaj (JK Science)
Introduction: The major leading cause of disease-related mortality in children is childhood cancer. It can be difficult to make an accurate diagnosis using only histopathology due to overlapping features and similar histomorphological appearances in various cancers. Immunohistochemistry (IHC) markers can help distinguish tumors that show similar histomorphological features. Aims & Objectives: This study was undertaken to evaluate the histopathological spectrum of pediatric solid malignant neoplasms with IHC and to assess the role of IHC in pediatric solid malignant tumors. Study Design: An observational study of resected malignant solid tumors in the pediatric population including Gross and Histopathological examination was conducted. Materials and methods: 55 samples were collected for five years. All samples were processed for routine histopathology and IHC was done on the majority of these samples. Results: The top five categories of tumors were retinoblastomas, lymphomas, neuroblastomas, bone and soft tissue tumors, and renal and reproductive system tumors. The mean age is 6.6 years and most commonly presented in 0-5 years of age constituting 30 cases. 35 cases seen were in male patients, and 20 in female patients. IHC was performed on 44 cases for confirmation of diagnosis. For the rest of the 11 cases, the histopathological study is the gold standard for diagnosis. Conclusion: An integrated approach including Histomorphological features is required for provisional diagnosis and IHC is necessary for final diagnosis and further characterization.